2000
DOI: 10.1038/modpathol.3880241
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cytokeratin 20 and CD44 Protein Expression with WHO/ISUP Grade in pTa and pT1 Papillary Urothelial Neoplasia

Abstract: The aim of this study was to assess the relationship of immunoreactivity of cytokeratin 20 (CK20) and CD44 across the spectrum of urothelial neoplasia using the WHO/ISUP consensus classification. A total of 120 papillary urothelial pTa and pT1 tumors (8 papillomas, 8 neoplasms of low malignant potential, and 42 low-grade and 62 high-grade carcinomas) were immunostained by using CK20 and CD44 antibodies. The relationships of tumor grade, pathologic stage, recurrences, and progression in stage with CK20 and CD44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
96
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 43 publications
(43 reference statements)
16
96
1
4
Order By: Relevance
“…Very limited studies have investigated the immunohistochemical profile of urothelial papillomas; cytokeratin 20 (CK20) has been analyzed in two studies (8,9), and standard isoform CD44 antibodies in one study (8). The findings corroborate the morphologic observation of normal-appearing urothelium on a fibrovascular stalk.…”
Section: Table 2 Summary Of Clinicopathologic Data Of Patients With supporting
confidence: 62%
See 3 more Smart Citations
“…Very limited studies have investigated the immunohistochemical profile of urothelial papillomas; cytokeratin 20 (CK20) has been analyzed in two studies (8,9), and standard isoform CD44 antibodies in one study (8). The findings corroborate the morphologic observation of normal-appearing urothelium on a fibrovascular stalk.…”
Section: Table 2 Summary Of Clinicopathologic Data Of Patients With supporting
confidence: 62%
“…The staining pattern with CK20 in urothelial papillomas in most cases is similar to that seen in normal urothelium (i.e., CK20 immunoreactivity is restricted to the umbrella cell layer with an absence of staining in the basal and intermediate cells) (8,9). CD44 expression in urothelial papillomas, like normal urothelium, is limited to the basal cell layer (8). In contrast, papillary urothelial neoplasms of low malignant potential and low-grade papillary transi- tional cell carcinomas show higher rates of CK20 and CD44 overexpression (8).…”
Section: Table 2 Summary Of Clinicopathologic Data Of Patients With mentioning
confidence: 66%
See 2 more Smart Citations
“…No statistical significant difference was detected; possibly due to the small number of cases showing normal expression. Desai et al 24 found that tumors with normal CK20 expression recurred less frequently than tumors with abnormal pattern, but with insignificant statistical difference (44.9% vs. 63.2%, p = 0.06). However, Harnden et al 25 revealed that disruption of normal CK20 expression was highly significantly correlated with recurrent tumors.…”
Section: Discussionmentioning
confidence: 99%